Rola katastrofalnych wezbrań w kształtowaniu morfologii koryt w małych zlewniach górskich, na przykładzie zdarzenia z maja 2014 r. w zlewni górnej Skawicy - Franczak, Paweł (Leśne Prace Badawcze, 2017)
Mountain streams are subjected to continuous reshaping of their river beds during floods with the greatest changes occurring during extreme floods caused by sudden and heavy rainfall. Riverbed transformations during these flash floods are more severe in forest areas, where wooden logs carried by the swollen streams are more likely to be deposited on the ground, which in turn leads to a greater accumulation of other transported material and debris. The study was conducted in the Rybny Potok catchment area (Babia Góra National Park). An extreme flash flood occurred on 15th – 16th May 2014 due to heavy rainfall, which, on 15th May amounted to 138 mm. The total amount of precipitation in the catchment area amounted to 216.5 mm in three days. This resulted in sudden and full spate streams, contributing to significant geomorphological transformation reaching all the way to the bottoms of the river beds. During the flash flood, already established river beds and streams increased in size and many new river courses were formed.